Nirsevimab for Prevention of RSV in Healthy Late-preterm and Term Infants. Issue 3 (24th September 2022) - Hammitt, L.L.; Dagan, R.; Yuan, Y.; Baca Cots, M.; Bosheva, M.; Madhi, S.A.; Muller, W.J.; Zar, H.J.; Brooks, D.; Grenham, A.; Wählby Hamrén, U.; Mankad, V.S.; et al.
Abstract : ( N Engl J Med . 2022;386:837–846. doi: 10.1056/NEJMoa2110275) Infants experience medically attended illness and hospitalization at elevated rates from respiratory syncytial virus (RSV) infection. As a monoclonal antibody with an extended half-life, Nirsevimab (N) is an emerging treatment that binds to the RSV fusion protein and has enhanced inhibitory potency for RSV in cell-culture and animal models over Palivizumab. Preterm (29 to <35 wk gestational age birth) infants receiving a single dose of N before RSV season showed 70.1% efficacy at protection against RSV with a favorable safety profile. The safety and efficacy of N in late-preterm and term infants entering their first RSV season is investigated in this phase 3 trial.